Advances in Solid Dispersion Technology: Method-Dependent Solubility Enhancement Approaches - Sonawane Gauri Madhukar,; Dr. Deepak D. Sonawane,; Abdul Kalam, (Asian Journal of Pharmaceutical Research and Development, 2026)
Solid dispersion technology is widely recognized as an effective approach for enhancing the solubility and oral bioavailability of poorly water-soluble drugs. A large number of newly developed pharmaceutical compounds belong to Biopharmaceutics Classification System (BCS) Class II and IV categories, where poor aqueous solubility limits dissolution and gastrointestinal absorption, resulting in reduced therapeutic efficacy. Solid dispersions improve drug dissolution through mechanisms such as particle size reduction, enhanced wettability, amorphization, reduced crystallinity, and increased surface area. This review highlights the fundamental concepts, mechanisms, classification, carriers, preparation methods, characterization techniques, recent advances, applications, and future prospects of solid dispersion technology. Various hydrophilic carriers including polyethylene glycol (PEG), polyvinylpyrrolidone (PVP), hydroxypropyl methylcellulose (HPMC), and Soluplus® are extensively used to enhance dissolution behavior and maintain supersaturation. Conventional techniques such as fusion and solvent evaporation, along with advanced technologies including hot-melt extrusion, spray drying, freeze drying, electrospinning, and supercritical fluid processing, are discussed in terms of their advantages, limitations, and industrial applicability. Recent innovations such as ternary solid dispersions, nanostructured systems, lipid-based formulations, artificial intelligence-assisted optimization, and continuous manufacturing have significantly improved formulation efficiency and scalability. Commercially available products demonstrate the successful industrial application of solid dispersions in oral drug delivery. However, challenges including physical instability, recrystallization, moisture sensitivity, and scale-up difficulties continue to affect formulation development. Future advancements in smart polymers, green manufacturing technologies, and personalized medicine are expected to further expand the potential of solid dispersion systems in modern pharmaceutical research and industry.